Identification of Three Novel O-Linked Glycans in the Envelope Protein of Tick-Borne Encephalitis Virus - Ebba Könighofer; Ekaterina Mirgorodskaya; Kristina Nyström; Karin Stiasny; Ambjörn Kärmander; Tomas Bergström; Rickard Nordén (Viruses)
The tick-borne encephalitis virus is a pathogen endemic to northern Europe and Asia, transmitted through bites from infected ticks. It is a member of the Flaviviridae family and possesses a positive-sense, single-stranded RNA genome encoding a polypeptide that is processed into seven non-structural and three structural proteins, including the envelope (E) protein. The glycosylation of the E protein, involving a single N-linked glycan at position N154, plays a critical role in viral infectivity and pathogenesis. Here, we dissected the entire glycosylation profile of the E protein using liquid chromatography-tandem mass spectrometry and identified three novel O-linked glycans, which were found at relatively low frequency. One of the O-linked glycans was positioned close to the highly conserved N-linked glycan site, and structural analysis suggested that it may be relevant for the function of the E 150-loop. The N154 site was found to be glycosylated with a high frequency, containing oligomannose or complex-type structures, some of which were fucosylated. An unusually high portion of oligomannose N-linked glycan structures exhibited compositions that are normally observed on proteins when they are translocated from the endoplasmic reticulum to the trans-Golgi network, suggesting disruption of the glycan processing pathway in the infected cells from which the E protein was obtained.